RISIKO PAJAK SEBAGAI PEMODERATOR PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PENGHINDARAN PAJAK - Widuri, Retnaningtyas; Abel, Jason Jan (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2021)
This study was conducted to examine the effect of corporate social responsibility and tax avoidance with tax risk as a moderating variable. This study was conducted on firms in the manufacturing sector in Indonesia. The sample used includes 132 companies listed on the Indonesia Stock Exchange during the 2014-2018 period. This study uses Moderated Regression Analysis (MRA) and is processed using SPSS version 22. The results of this study provide evidence that businesses that better disclose corporate social responsibility, measured by giving, are less likely to engage in tax avoidance activities. However, there are tax risks that a business has to pay attention to. This study also finds that tax risk can be moderated by weakening the effect of corporate social responsibility on tax avoidance.